Paesaggi di coesistenza, ovvero come attorno ad un passeriforme si articola l’abitare in una zona di montagna - Lia Zola (EtnoAntropologia)
Landscapes of coexistence is a term used by a team of zoologists in a 2019 article referring to the degree of tolerance between a population of lions and humans within three African natural parks and meant as «the sustainable cohabitation of people and lions within a shared landscape» [Western et al. 2019, 204). Based on field research carried out in three alpine valleys, Valle Susa, Val Chisone and Val Troncea, my essay tries to broaden the understanding of landscapes of coexistence by arguing that they are complex sites of relationships where humans and non humans alike shape and co-shape them through interactions but also frictions and conflicts that revolve around a small bird, Petronia petronia.